Effects of yeast, essential oils, increased zinc oxide and copper sulfate, or their combination in nursery diets on pig performance - Langemeier, Austin James (Kansas State University, 2017)
Two experiments evaluated the effects of feeding growth promoting alternatives, alone or in combination, on nursery pig performance in comparison to a common feed additive, carbadox. In Exp.1, 288 weaned pigs (Line 600 × 241; DNA, 5.36 kg) were used in a 42-d study. Pigs were allotted to 1 of 9 dietary treatments in pens of 4 at weaning in a randomized complete block design with 8 replications per treatment. Dietary treatments were arranged with a negative control diet with no dietary feed additive, a positive control with added carbadox or 7 treatments including added copper sulfate (CuSO₄; 0 vs. 125 ppm Cu) and added zinc oxide (ZnO; 0 vs. 3,000 ppm Zn from d 0 to 7 and 2,000 ppm Zn from d 7 to 28), essential oils from XTRACT 6930 at 0.91 kg/ton, Safman (yeast cell walls) at 0.23 kg/ton , Biosaf HR (yeast cells) at 0.68 kg/ton. These supplements were fed alone or in combination. From d 0 to 7 experimental diets were a pelleted diet and fed in a meal form from d 7 to 28, followed by a common corn-soybean meal-based diet from d 28 to 42. Essential oil blend (cinnamaldehyde) and yeast had no (P > 0.05) effect on ADG. Feeding carbadox or added trace minerals (Cu and Zn) improved ADG (P < 0.05) of nursery pigs compared to the control. Carryover effects from any of these dietary treatments on subsequent growth performance were not (P > 0.05) different. The use of added trace minerals Cu and Zn alone or in conjunction with either yeast or essential oil blend (cinnamaldehyde) results in ADG and G/F comparable to carbadox. In Exp. 2, 280 weaned pigs (Line 600 × 241; DNA, 5.18 kg) were used in a 35-d study. Pigs were allotted to 1 of 7 dietary treatments in pens of 5 at weaning in a randomized complete block design with 8 replications per treatment. Dietary treatments were arranged with a negative control diet with no dietary feed additive, a positive control with added carbadox or 5 treatments including added copper sulfate (CuSO₄; 0 vs. 125 ppm Cu) and added zinc oxide (ZnO; 0 vs. 3,000 ppm Zn from d 0 to 7 and 2,000 ppm Zn from d 7 to 35), and Victus® LIV (145 or 435 ppm). These supplements were fed alone or in combination (Cu/Zn and 145 ppm Victus® LIV or Cu/Zn and 435 ppm Victus® LIV. Diets were fed in meal form. Feeding carbadox, 145 ppm Victus® LIV or added trace minerals (Cu and Zn) improved ADG (P < 0.05) of nursery pigs compared to the control. In summary, under the conditions of these experiments, pigs fed zinc/copper, 145 ppm Victus® LIV or a combination of these had similar (P > 0.05) growth performance to pigs fed carbadox.
Keywords: Essential oil; Nursery pig; Yeast; ZincAlternative; Copper